Expression of Dectin-1 in Patients with Acute Appendicitis: A Case-Control Study (International Journal of Environmental Sciences, 2025)
Background: Acute appendicitis is a prevalent surgical emergency characterized by inflammation of the appendix and intricate immunological reactions. Dectin-1 is a C-type lectin receptor in mammals that serves as a pattern recognition receptor, detecting fungal infections and activating several signaling pathways. Dectin-1 specifically detects β-glucans on the surface of fungal yeast cells.Objectives This study aimed to estimate the concentrations of Dectin-1 in both serum and appendix tissue following appendectomy. Material and Methods: A total of 100 specimens (blood and tissue) were collected from individuals aged 14 to 65 years of both sexes who underwent treatment for appendicitis at a teaching hospital in Iraq between September and December 2024. Dectin-1 concentrations were measured using enzyme-linked immunosorbent assay (ELISA).Results: The mean blood Dectin-1 level in appendicitis patients was 601.21 ± 332.11 ng/L, whereas it was 588.16 ± 238.59 ng/L in the control group. There was no significant difference between the groups (P = 0.902). The average tissue concentration of Dectin-1 in appendicitis patients was 693.45 ± 300.76 ng/L, greater than the serum level, but not statistically significant (P = 0.402).Conclusions: These findings suggest a potential localized increase in Dectin-1 expression within the appendix tissue during inflammation, despite stable systemic levels in the bloodstream.